Growth Performance and Health Status of Giant Gouramy (Osphronemus gouramy Lac.) Seed Feeded With A Combination of Chitosan and Probiotic Supplements (Sinbiotic) - Fitram Novian; Roffi Grandiosa; Dra Rosidah; Dian Yuni Pratiwi (UNIVERSITAS MUHAMMADIYAH PONTIANAK, 2023)
ABSTRACT This study aims to determine the optimum level of addition of chitosan to the feed to increase the growth rate and daily feed consumption of giant gouramy. The method used in this research is an experimental method using a completely randomized design (CRD), which consists of five treatments and four replications. The treatments used were (A) giving 2.5 g/kg chitosan and 5 g/kg probiotics, (B) 5 g/kg chitosan and 5 g/kg probiotics, (C) 7 chitosan, 5 g/kg and 5 g/kg probiotics, (D) 10 g/kg chitosan and 5 g/kg probiotics, (E) without chitosan and probiotics (control). The test fish used were giant gouramy with a length of 7-9 cm and a weight of 7-9 g. The container used was hapa measuring 1 x 1 x 1 m3 as many as 20 pieces with a density of 20 fish for each treatment and 42 days of maintenance. The amount of feed given was 5% of the fish biomass. Data from observations of length and weight were analyzed using Analysis of Variance (ANOVA) with a 95% confidence level, if there was a significant difference, Duncan's multiple distance test was performed. The results showed that synbiotics administration of 7.5 g/kg chitosan and 5 g/kg probiotics on feed gave the best results with the highest absolute length growth of 4,48 ± 0,3 cm, the highest absolute weight growth of 24,03 ± 3,1 g, the highest daily growth rate of 57,20 ± 7,3 %, feed conversion ratio the lowest was 1.6 ± 0,3 and the highest survival was 98,8 ± 3,2 % in giant gouramy. Keywords: giant gouramy, synbiotic, growth,chitosan,probiotic